5 - A Search for Post-apartheid Collective Identities: Ethnic Student Organisations at a South African University - Sikwebu, Dinga (Journal of Higher Education in Africa, 2008)
Scholarship on higher education decries the levels of student activism in post- apartheid South Africa. It argues that student organisation is sporadic, fragmented and unrepresentative of broad student layers. Because of its emphasis on political identities as well as the failure to define activism broader than protests, this as- sessment fails to recognise the myriad of organisations such as cultural and reli- gious bodies in South African universities today. By ignoring these forms of or- ganisation, the literature that emphasises the decline in student activism after the demise of apartheid not only ignores initiatives where students are organising around their ‘new’ identities, but also fails to appreciate how historically these ‘hold-over’ organisations connected one wave of protest to the other. Using the University of the Witwatersrand (Wits) as a research site, this article focuses on ethnic identities as a significant feature around which a section of the student population is organising. The paper looks at how the disappearance of legal apart- heid, the new political environment as well as the failure of traditional political student movements to organise around their constituency’s multiple identities, have provided space and impetus for new forms of organisation.